Analisis Pola Peresepan Obat Asma pada Anak Di RS. Rotinsulu Bandung - Alief Ergin Az-Zikra Husaeni; Bambang Tri Laksono; Andrian Hoerul Anwar (UNISBA Press, 2026)
Abstract. Asthma is a chronic inflammatory disease of the airways characterized by bronchial hyperresponsiveness and recurrent symptoms such as shortness of breath, coughing, and wheezing. According to the Global Initiative for Asthma (GINA) report in 2023, more than 262 million people worldwide are living with asthma, making it a significant global health problem, particularly among children. This study aimed to analyze the prescribing patterns of asthma medications in pediatric patients at Dr. H.A. Rotinsulu Lung Hospital, Bandung, during the period from January 2020 to December 2024. The research employed a descriptive study design with a cross-sectional approach and retrospective data collection. Data were obtained from medical records and prescription records of pediatric asthma patients aged 0–18 years who were diagnosed with ICD-10 codes J45.x–J46.x. A total sampling technique was applied, resulting in 100 prescription records that met the inclusion and exclusion criteria. The results showed that asthma prevalence was slightly higher in male children (52%) compared to female children (48%). Based on age distribution, asthma cases were most frequently observed in adolescents aged 12–18 years (49%). Regarding prescribing patterns, the most commonly used class of medication was Short-Acting Beta Agonists (SABA), accounting for 46% of prescriptions, with salbutamol being the most frequently prescribed drug. Other medications prescribed included Short-Acting Muscarinic Antagonists (SAMA), Inhaled Corticosteroids (ICS), Long-Acting Beta Agonists (LABA), and Leukotriene Receptor Antagonists (LTRA). Abstrak. Asma merupakan penyakit peradangan kronis pada saluran napas yang ditandai dengan hiperreaktivitas bronkus dan gejala berulang seperti sesak napas, batuk, serta mengi. Berdasarkan laporan Global Initiative for Asthma (GINA) tahun 2023, lebih dari 262 juta orang di dunia hidup dengan asma. Penelitian ini bertujuan untuk menganalisis pola peresepan obat asma pada pasien anak di Rumah Sakit Paru Dr. H.A. Rotinsulu Bandung selama periode Januari 2020 hingga Desember 2024. Penelitian menggunakan desain deskriptif dengan pendekatan cross-sectional dan pengambilan data retrospektif dari rekam medis serta catatan resep pasien asma anak usia 0–18 tahun yang terdiagnosis dengan kode ICD-10 J45.x–J46.x. Teknik pengambilan sampel dilakukan secara total sampling dan diperoleh 100 data resep yang memenuhi kriteria inklusi dan eksklusi. Hasil penelitian menunjukkan bahwa prevalensi asma pada anak laki-laki sedikit lebih tinggi (52%) dibandingkan anak perempuan (48%). Berdasarkan kelompok usia, kasus asma paling banyak ditemukan pada usia remaja 12–18 tahun (49%). Profil peresepan menunjukkan bahwa golongan obat yang paling sering digunakan adalah Short-Acting Beta Agonist (SABA) sebesar 46%, dengan salbutamol sebagai obat yang paling banyak diresepkan. Selain itu, obat lain yang juga digunakan meliputi Short-Acting Muscarinic Antagonist (SAMA), Inhaled Corticosteroid (ICS), Long-Acting Beta Agonist (LABA), dan Leukotriene Receptor Antagonist (LTRA).